Achieving superior strength-ductility synergy in CoCrNi medium entropy alloy with a novel bionic brick-mud structure - Pengcheng Ma; Jiongxian Li; Jiangjie Liao; Feng Ye; Yu Liu; Hai Huang; Jing Qiu; Mian Chen; Jian Hu (Materials Research Letters)
In recent years, the concept of heterogeneous structure (HGS) strengthening has garnered significant attention due to its superior performance relative to conventional strengthening methods. This study presents a novel bionic brick-mud structure designed to enhance the mechanical properties of CoCrNi medium entropy alloy (MEA). The varying surface hardness between the mud and brick regions activates heterogeneous deformation-induced (HDI) hardening, while internal lattice defects, twin networks, and chemical short-range orders (CSROs) synergistically interact with dislocations. This distinctive structural design results in a remarkable balance between strength and ductility, demonstrating a strengthening effect that surpasses those observed in previous studies.